Lessons from project-scale reducing emissions from deforestation and forest degradation: A case study in northern Lao People’s Democratic Republic - Hiratsuka, Motoshi; Hashiguchi, Hozumi; Toda, Miki; Yamanoshita, Makino Yamada (Frontiers in Forests and Global Change, 2022)
Reducing emissions from deforestation and forest degradation (REDD+) has been implemented over the past decade, and has led to a restructuring of forest governance systems in host countries. In the case of the Lao People’s Democratic Republic, which is promoting REDD+, activities have been implemented at national, sub-national and project scales. Project scale REDD+ is assumed to be compatible with small-scale forestry, and usually targets local people to enhance participatory forest management through technology transfer. Such projects were also supported under bilateral cooperation or by private funds. In the case of national or sub-national scale REDD+, the central government of Lao People’s Democratic Republic aims to develop a system of forest monitoring, as well as related structures required by international REDD+ entities. These activities are supported with substantial funding from multilateral organizations. Lessons learned from project scale REDD+ in northern Lao People’s Democratic Republic showed a gap in expectations among different donors and recipients regarding how to implement REDD+, and particularly how to reduce dependency on forest resources in rural areas, and how to estimate and account for greenhouse gas emission reductions with consistent methodologies at different scales. Such differences are related to the attitudes of local people toward participation, and of the private entities that fund projects and ground-based activities. In future REDD+ schemes, the structural network or structural social capital among national, sub-national and project-scale activities should be re-considered to enhance the continued participation of stakeholders and to use their accumulated experience and knowledge of small-scale forestry management.